If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(5 + -5m) = 0 (5 * -5 + -5m * -5) = 0 (-25 + 25m) = 0 Solving -25 + 25m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 25m = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 25m = 0 + 25 25m = 0 + 25 Combine like terms: 0 + 25 = 25 25m = 25 Divide each side by '25'. m = 1 Simplifying m = 1
| 6(3+5x)-5=43 | | 2(-2x+3)=20+6 | | 2970x(198x-178)-7921=0 | | -5t^2+40t+100=0 | | 2970(198x-178)-7921=0 | | -1.4(x-15)=2.4(x-0.5) | | 3p+2=-29 | | 2k^2-9k+11=4 | | 4(a-8)=-48 | | 3(y-2)+15=-5(y-7)-10 | | y^2=-4y-10 | | 5n+6-3n=3.7 | | 4x+3y+6z=2825 | | 72=6x+4(x-12) | | 4k+h=-2k-144 | | 4x-134+18=4x-32 | | x(x-6)= | | 6(6x-6)+6=8x-8 | | 3j+4=19 | | 7x+8-22=44-7x | | 2x^2+6x-5=85+x^2+1 | | 30(198x-178)-7921=0 | | Y+18=5y-10 | | 4+2r=10 | | 3(y-2)+15=-5(q-7)-10 | | 115=2x+7(4x-5) | | -8w-14=34 | | 4+2g=8 | | b+(-42)=(-86) | | y^2-4y-x^2+4=0 | | 15(198x-178)-7921=0 | | 4x-5=-4+6+6x-1 |